(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This study aimed to explore the relationship between physicians’ personal engagement in health-promoting physical activity (PA) and their practices in counselling patients about PA. Methods: A quantitative research design was employed, involving 202 physicians who completed an online survey. The Health and Exercise subscale of the Lifestyle and Habits Questionnaire-Brief (6 items) was used to assess participants’ PA-related health behaviours. Responses were rated on a five-point Likert scale (1 = never, 5 = very often), with higher scores indicating more favourable health-promoting behaviour. Physicians’ frequency of counselling patients on PA was measured using a five-item scale adapted from validated PA promotion questionnaires, also rated on a five-point Likert scale. Data were analysed using IBM SPSS Statistics version 29 software. Results: Of the participants, 44.1% were categorised in the Middle range of health-promoting PA engagement, while 26.7% and 29.2% fell into the Bottom and Top ranges, respectively. A higher proportion of females were in the Middle range (51.6%), while more males were in the Bottom range (41.3%) (p < 0.001). Physicians most frequently asked patients about their PA (mean (M) = 3.28, standard deviation (SD) = 1.20) and advised them to explore the health benefits of PA (M = 3.22, SD = 1.16), though these actions were generally infrequent. Follow-up on patients’ PA progress was the least common behaviour (M = 2.53, SD = 1.32). A statistically significant relationship was found between physicians’ own PA-related health behaviours and the frequency of their PA counselling. Conclusion: Physicians’ personal engagement in physical activity significantly influences their clinical counselling practices. Continuous development of PA-related competencies may enhance future patient-centred care and promote more frequent and effective PA counselling in clinical settings.